Parental attitudes and perceptions towards the recruitment of children to clinical trials: a cross-sectional survey - Safra, Ibrahim Farhan; Alnaimi, Shaikha Jabor; Gad, Gehad; Abraham, Aliamma; Al-Hammadi, Ahmad Hassan; Bayoumi, Mohammad A. A.; Alyafai, Fawziya; Gad, Ashraf (Frontiers in Pediatrics, 2024)
Clinical trials (CTs) in children are critical for understanding and treating childhood diseases.However, CTs on children require prior permission from parents. We evaluated the parental attitudes and perceptions regarding the recruitment of their children in CTs.We used a cross-sectional survey questionnaire targeting parents of children admitted to the neonatal and pediatric departments in two tertiary hospitals in Qatar. The survey was administered by investigators and was composed of two domains to assess the knowledge and attitude of parents regarding children's recruitment in CT, in addition to the participant's demographics domain.Of the 167 questionnaires offered to parents, we received a total of 138 responses, resulting in a response rate of 82.6%, with the majority being women (72%). Many parents (75%) expressed willingness to recruit their children for CTs. However, 66% opposed new experimental treatments for their child, while 41% agreed to new treatments if they had previously been used in the medical field. Logistic regression analysis revealed key predictors influencing parents' decisions to participate in CTs, including having a newborn (aOR = 17.651, p<0.001), families with five or more members (aOR = 3.293, p=0.012), collecting blood samples (aOR = 8.602, p=0.003), performing additional tests on collected samples (aOR = 4.115, p=0.046), belief in helping others (aOR = 8.744, p=0.002), and the option of home therapy (aOR = 7.090, p=0.004).Many parents are open to enrolling their children in CTs, particularly when treatments have been previously used. Factors like having a newborn, large family size, blood collection, additional tests, and home therapy influence their decisions. Clear communication can enhance recruitment in pediatric trials.